A new deep-water species of Natatolana (Crustacea: Isopoda: Cirolanidae) from the Chatham Rise, eastern New Zealand - Bruce, Niel L. (Zootaxa, 2003)
Natatolana rekohu sp. nov. from the Chatham Rise, off southeastern New Zealand is described and figured. Natatolana rekohu was collected at a depth of 2799 metres, close to the greatest recorded depth for this genus. The species is a scavenger, and was feeding on dead fish in a sediment trap. Natatolana rekohu is characterised by: reduced eyes; strongly indented anterior margin of the head; pentagonal frontal lamina, with weakly convex lateral margins; pleonites 1 and 2 not produced, 3 weakly and pleonite 4 rounded; pereopods 1 and 2 usually with 5 or 6 setae on the propodal palm. In males the large flat and widely separated penes and the strongly curved, wide and terminally toothed appendix masculina are additional diagnostic characters. As in most Natatolana the numbers of robust setae on the margins of the uropodal rami and pleotelson are also important in making a correct identification.